2003
DOI: 10.1038/sj.bjc.6601445
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy or best supportive care? A prospective study explaining patients' treatment preference and choice

Abstract: In palliative cancer treatment, the choice between palliative chemotherapy and best supportive care may be difficult. In the decisionmaking process, giving information as well as patients' values and preferences become important issues. Patients, however, may have a treatment preference before they even meet their medical oncologist. An insight into the patient's decision-making process can support clinicians having to inform their patients. Patients (n ¼ 207) with metastatic cancer, aged 18 years or older, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
1
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 47 publications
5
88
1
4
Order By: Relevance
“…Our data indicate a significant preference for quality over length of life up to six months post-diagnosis in advanced lung cancer patients, which is a new finding supported by previous related literature [6,7,25]. Preference for quality was independent of smoking status.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our data indicate a significant preference for quality over length of life up to six months post-diagnosis in advanced lung cancer patients, which is a new finding supported by previous related literature [6,7,25]. Preference for quality was independent of smoking status.…”
Section: Discussionsupporting
confidence: 79%
“…A high score on the Q scale indicates a high value for quality of life over length and a high score on L indicates a preference for length of life over quality. The QQQ has demonstrated validity for use with cancer patients: internal reliability scores range from 0.68-0.75 for Quality and 0.67-0.79 for Length [6,7,25].…”
Section: Quantitative Measuresmentioning
confidence: 99%
“…In essence, there are differences in opinion in the valuing of toxicity and survival between doctors and patients, along with wide variation in beliefs within both These factors underscore the importance of considering the impact of these factors in treatment choices as they may ultimately impact on the survival and quality of life of the patients. Clinicians must be attentive to the decision-making style of the patient [8], their desired level of involvement in treatment decisions [28] and cognitive and affective determinants of patient choice [22] as these seem to influence patient decisions regarding chemotherapy for lung cancer, although their impact is not well understood. The complexities of these decisions underscores the importance of a multidisciplinary approach and the need to obtain the perspectives of all clinicians involved in care [30].…”
Section: Discussionmentioning
confidence: 99%
“…A review of determinants of cancer patient preferences concluded that patients are more positive toward adjuvant treatment in the context of larger benefits, less toxicity, personal experience of the particular treatment and having dependents, especially children living at home [22]. One study found patients' preference to undergo chemotherapy treatment was positively explained by striving for length of life and negatively by striving for quality of life [8]. Other factors suggested as influencing patients' attitudes to treatment and treatment decisions include parenthood status, personal experience of illness, health literacy, functional status and quality of life indicators [23][24][25][26].…”
Section: Perceptions Of Lung Cancer Patients: Balancing Risks and Benmentioning
confidence: 99%
See 1 more Smart Citation